PENGARUH PENERAPAN TERAPI KOMPLEMENTER : MORINGA OLEIFERA DALAM MENINGKATKAN PRODUKSI ASI PADA IBU DI WILAYAH PUSKESMAS TALISE KELURAHAN TONDO - Arinda Alya Inayah; Ardin S Hentu; Maryam Maryam; Lilik Utami (An Idea Health Journal, 2022)
Breast milk or mother's milk is food or drink that is given to children without any other bonus food that is given for 6 months. Information from the Earth Health Organization (World Health Organization) in general, the value of exclusive breastfeeding on earth, currently around 38%. In Indonesia, although most women (96%) breastfeed their children in their lifetime, only 42% of children under 6 months of age are exclusively breastfed. Based on the results of interviews with nurses at the Talise Health Center, they reported that the data on the percentage of exclusive breastfeeding at the Roviga sub-health center in 2018 was 57%, 2019 was 59%, and in 2020 it was 55%. This research method is quantitative research through observation checklist sheets and interviews, by asking questions related to the research project, then data is collected and analyzed with a large sample of 15 mothers who are breastfeeding. The results of this study were obtained from 15 respondents studied, there were 12 respondents who said they experienced an increase in breast milk production after consuming Moringa Oleifera Therapy with a percentage of 80.0% and there were 3 respondents who did not experience an increase in breast milk production after consuming Moringa Oleifera Therapy with a percentage of 20.0%. the conclusion is that there is an effect of giving Moringa Oleifera Therapy in increasing and facilitating breast milk production.